Automated technology for verification and analysis 10th International Symposium, ATVA 2012, Thiruvananthapuram, India, October 3-6, 2012. Proceedings - Mukund, Madhavan; Chakraborty, Supratik (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed proceedings of the 10th International Symposium on Automated Technology for Verification and Analysis, ATVA 2012, held at Thiruvananthapuram, Kerala, India, in October 2012. The 25 regular papers, 3 invited papers and 4 tool papers presented were carefully selected from numerous submissions. Conference papers are organized in 9 technical sessions, covering the topics of automata theory, logics and proofs, model checking, software verification, synthesis, verification and parallelism, probabilistic verification, constraint solving and applications, and probabilistic systems.